Saldanha Bay Industrial Development zone: Co-ordination as a determining factor of opportunity lost or gamechanger - Moses, Denver (Graduate School of Development Policy and Practice, 2017)
As a fledgling democracy, South Africa has had to contend with a slowing economy that has been accompanied by increasing unemployment. The Industrial Development Zone (IDZ) is one of the policy instruments used by the South African government in an attempt to overcome these challenges. This research study takes a closer look at this policy instrument within the specific context of the Saldanha Bay IDZ. Saldanha Bay is an operating port on the West Coast of South Africa which, after a series of feasibility studies, has been deemed a suitable location to establish a services hub for upstream oil and gas activities. Its competitive advantages are inter alia a naturally deep port and close proximity to Cape Town. This study seeks to construct a rich narrative that unravels key activities that emerged from the project's conceptual phase through to its implementation phase. This is a period of a little less than two decades stretching from around 1999 to 2016. In linking this narrative to a timeline, this dissertation explores three central issues. The first is whether the Saldanha Bay IDZ presents a commercially viable option for investors. Secondly, it explores whether the public sector has been able to establish the necessary enabling environment required for project success. Finally, it seeks to determine the factors that influenced the speed of project delivery. This narrative is built by having conversations with key stakeholders from both the private and public sectors who have had an involvement with the project for a considerable amount of time. The intention is to extract lessons from their journey and use these learnings as a basis to improve stakeholder co-ordination in this and other projects characterised by multiple actor and principal relationships.